Empirical evidence for large‐scale human impact on intertidal aggregations, larval supply and recruitment of Pyura praeputialis around the Bay of Antofagasta, Chile. (24th May 2016) - Manríquez, Patricio H.; Castilla, Juan Carlos; Ortiz, Verónica; Jara, María Elisa
Abstract: In northern Chile, Pyura praeputialis is an invasive species inhabiting rocky intertidal and subtidal habitats restricted exclusively to the Bay of Antofagasta where it forms extensive aggregations. The negative impact of Pyura gathering on mid‐intertidal abundances of this species has recently been reported at the south‐eastern end of this bay. In the present study we have increased sampling sites to cover the entire bay toward the north‐western end and the northern section, where a coastal marine reserve for the scallop fishery partially restricts shellfish gathering. Therefore, the sampling sites were chosen to represent different levels of shellfish gathering access along the northern shore of the bay. Long‐term monitoring (1999–2014) of changes in tunicate cover and the abundances of larvae and recruits at seven sites are reported. The opening of a remodelled artificial and recreational beach in 2012, on the central‐eastern shore of the bay, has increased accessibility to rocky intertidal platforms that started to be massively visited by Pyura gatherers from the summer of 2013. This allowed for the implementation of an intensive short‐term monitoring program of changes in tunicate cover and the abundances of their larvae and recruits. When gathering access was present the reduction in intertidal cover was generalized to the entire bay and followed by reductions in larvae and recruits. However, these reductions were not found in sites with more restricted gathering access. We conclude that continuous extraction by Pyura gatherers followed by reductions of conspecific larvae and recruits are the main drivers behind the reduced abundance of P. praeputialis in the entire bay of Antofagasta. Thus, if gathering is not stopped important ecosystem services provided by this tunicate in the bay may be threatened. Similar consequences may be expected if other massive and irreversible reductions in other species of the Pyura complex, that inhabit other coasts in the southern hemisphere, occur. The controversy concerning the impacts of invasive species and whether they cause negative, positive or neutral impacts to original ecosystems and fisheries is discussed.